CFD analysis of chest fairings in time trial cycling - Blocken, B.; Malizia, F.; van Druenen, T. (Journal of Wind Engineering and Industrial Aerodynamics, 2024)
In the past but especially more recently, some cyclists in triathlon and road cycling competitions have been riding with an object stuck between their chest and their shirt, attempting to reduce aerodynamic drag. This object has been referred to as "chest fairing". The most excessive examples occurred in triathlon, where large objects such as drink bottles were used as chest fairing. More exceptionally, smaller examples have been observed in road cycling in individual time trials (ITT), including the 2023 Tour de France ITT and the 2023 Glasgow Road World Championships ITT. To the best of our knowledge, this paper provides the first published scientific assessment of the benefits that can be obtained by different types of chest fairings. The assessment is performed by computational fluid dynamics (CFD) simulations validated with wind tunnel tests. A reference configuration of cyclist without chest fairing and seven chest fairing configurations are analysed. The resulting drag reduction can go up to 3.6%, but some chest fairings actually increase the drag. It is concluded that a chest fairing can be beneficial and potentially decisive but that careful and dedicated a priori wind tunnel tests or CFD simulations for the specific rider must be undertaken.